A new era for Chinese military logistics. Issue 3 (2nd September 2021) - Wuthnow, Joel
ABSTRACT: The PLA's ability to project force within and beyond China's borders, which Chinese strategists refer to as "strategic delivery, " depends on adequate logistics capabilities, systems, and policies. The new Joint Logistic Support Force will play a critical role in these respects. The force, established in 2016 as part of Xi Jinping's reforms, made its operational debut in the PLA's response to the novel coronavirus outbreak in Wuhan in 2020. That case provides details about the JLSF's structure, capabilities, and operations. Leveraging insights from that case, the essay portrays the JLSF as a force in transition, both the inheritor of decades of investments in logistics modernization and recent upgrades, but also a new and largely untested force with several apparent weaknesses. Unless further improvements are made, the JLSF could be a weak link in future Chinese joint operations.